2009
DOI: 10.1002/ejic.200900646
|View full text |Cite
|
Sign up to set email alerts
|

The Borane Complexes Htbo·BH3 and Htbn·BH3 (Htbo = 1,4,6‐Triazabicyclo[3.3.0]oct‐4‐ene, Htbn = 1,5,7‐Triazabicyclo[4.3.0]non‐6‐ene): Synthesis and Dehydrogenation to Dinuclear Boron Hydrides

Abstract: Herein we report on the synthesis and characterization of the new borane adducts Htbo·BH 3 and Htbn·BH 3 (two isomers), where Htbo = 1,4,6-triazabicyclo[3.3.0]oct-4-ene and Htbn = 1,5,7-triazabicyclo[4.3.0]non-6-ene. Thermal treatment of these adducts leads to dihydrogen elimination and the formation of dinuclear boron hydrides with bridging guanidinate ligands, namely [BH 2 (µ-tbo)] 2 and [BH 2 (µ-tbn)] 2 , which both adopt boat-type conformations in the solid state. The experimental studies are accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
1
25
0
4
Order By: Relevance
“…The B 2 L 2 unit has a roof‐type structure, with one CH hydrogen pointing towards the roof and the other one away. The B−B bond length is 1.752(4) Å and is very close to the value of 1.753(4) Å found in {[B(μ‐hpp)(NHMe 2 )] 2 } 2+ , and diborane(4) compounds with other bridging guanidinates …”
Section: Resultssupporting
confidence: 77%
“…The B 2 L 2 unit has a roof‐type structure, with one CH hydrogen pointing towards the roof and the other one away. The B−B bond length is 1.752(4) Å and is very close to the value of 1.753(4) Å found in {[B(μ‐hpp)(NHMe 2 )] 2 } 2+ , and diborane(4) compounds with other bridging guanidinates …”
Section: Resultssupporting
confidence: 77%
“…For comparison, in the case of [H 2 B(µ-hpp)] 2 (dissolved in toluene), [H 2 B(µ-tbo)] 2 and [H 2 B(µ-tbn)] 2 (dissolved in benzene), triplets centered at -2.30, -10.81 and -5.73 (isomer in which each boron atom is attached to a five-and a six-membered ring) as well as -4.32/ -7.41 ppm (isomer in which one boron is attached to two five-membered rings and the other to two six-membered rings), respectively, were found in the 11 B NMR spectra. [32,20] In the case of [{HB(µ-hpp)} 2 (µ-H)] + featuring a bridging hydride, the 11 B NMR shift measures -2.2 ppm. [16] A strong band in the IR spectrum at 2359 cm -1 can be assigned to stretching modes ν(B-H).…”
Section: Reaction With Elemental Sulfurmentioning
confidence: 99%
“…Our work is motivated by a simple structure-reactivity concept. Hence the reactivity can be effectively controlled by the ring sizes of the guanidinate (see below), [20] and also of course by the group 13 element used. [21,22] …”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the related diboranes [H 2 B(tbo)] 2 and [H 2 B(tbn)] 2 (see the Lewis structures in Scheme ) with the deprotonated guanidines 1,4,6‐triazabicyclo[3.3.0]oct‐4‐ene (Htbo) and 1,5,7‐triazabicyclo[4.3.0]non‐6‐ene (Htbn) as bridging substituents 50. For these two molecules, a catalytic dehydrogenation was impossible, and the dehydrocoupling reactions were calculated to be endergonic.…”
Section: Resultsmentioning
confidence: 99%
“…For these two molecules, a catalytic dehydrogenation was impossible, and the dehydrocoupling reactions were calculated to be endergonic. On the other hand, the synthesis of [{Me 2 (H)NB(tbn)} 2 ] 2+ dication salts showed that BB bonding in the presence of tbn bridges is in principal possible 50. Therefore, we tested if hydride abstraction from [H 2 B(tbo)] 2 and [H 2 B(tbn)] 2 leads to the formation of cations that could subsequently be transformed into [HB(tbo)] 2 and [HB(tbn)] 2 by deprotonation.…”
Section: Resultsmentioning
confidence: 99%